Closing the research-to-practice gap: Using a plan-do-study-act approach to test innovative interventions to increase HPV immunization uptake in Canada - Navdeep Sandhu; Mika Rathwell; Aine Dolin; Thilina Bandara; Mulugeta Wondim; Cory Neudorf (Canadian Journal of Public Health, 2026)
Abstract In 2020, the Canadian Partnership Against Cancer commissioned the Urban Public Health Network to lead a multi-phased project to identify the inequalities and barriers to HPV vaccination for school-aged children across Canada. In Phase One, the UPHN team collaborated with public health and community partners across Canada to identify barriers to vaccination at a sub-jurisdictional and sub-populational level using a multiple methods approach. In Phase Two, UPHN is working with existing and new partners to achieve system-level outcomes through developing and testing innovative education and program delivery strategies to increase HPV immunization in school-based programs, using findings from Phase One. A Plan, Do, Study, Act (PDSA) framework, a core component of the Quality Improvement (QI) Model for Improvement, to implement quality improvement programs has been foundational in the development of and approach to these projects. In this commentary, we suggest that a PDSA framework offers an effective stepwise strategy to promote continuous learning, evaluation, and refinement of innovative practices, particularly in complex systems.